(untitled) (Unizik Journal of Chemical and Environmental Engineering, 2026)
This study investigates the sustainable removal of phenol from real pharmaceutical wastewater using carbonized rice husk (RH) as a low-cost agro-waste-derived adsorbent. The adsorbent was prepared through combined thermal and chemical activation to enhance surface properties, and its characteristics were examined using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Batch adsorption experiments were conducted to evaluate the effects of pH, adsorbent dosage, contact time, temperature, and initial phenol concentration. Equilibrium data were best described by the Langmuir isotherm model (R² = 0.9872), indicating monolayer adsorption with a maximum adsorption capacity of 66.5 mg/g. Kinetic analysis showed that the pseudo-secondorder model (R² = 0.9805) provided the best fit, suggesting that adsorption is governed by surface interactions. Thermodynamic parameters revealed that the adsorption process is spontaneous and exothermic, with ΔG values ranging from –12.73 to –10.76 kJ/mol and ΔH = –37.98 kJ/mol. Response Surface Methodology (RSM) based on Central Composite Design (CCD) was employed to model and optimize the adsorption process. The model was statistically significant (F = 21.40, p < 0.0001) with a high coefficient of determination (R² = 0.9365). Optimal conditions resulted in a maximum phenol removal efficiency of 99.83%. The findings demonstrate that carbonized rice husk is an efficient, sustainable, and economically viable adsorbent for phenol removal from complex wastewater systems, with strong potential for practical application and scale-up.